2011
DOI: 10.1177/039463201102400313
|View full text |Cite
|
Sign up to set email alerts
|

An Italian Study on Health-Related Quality of Life and Fatigue in Patients with Chronic Fatigue Syndrome and Patients with Chronic HCV Virus Infection: Similarities and Differences

Abstract: Severe fatigue and a significantly reduced health-related quality of life (HRQoL) have been described in patients with chronic fatigue syndrome (CFS) in comparison with patients affected by chronic hepatitis C (CHC) and other chronic medical conditions. We examined 39 CFS and 49 CHC patients to explore whether fatigue and a poor HRQoL represent a greater medical and social problem in CFS than in CHe. The severity of fatigue and the HRQoL were assessed using the Fatigue Impact Scale (FIS) and the Health Status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Sociodemographic characteristics such as residence in the west of China, stable marital status, high family income have been found to be favorable to better quality of life for patients with HCV infection. Although the association between gender and HRQoL was not significant in our study, women still reported more problems in dimensions of pain/discomfort (OR = 1.746; 95% CI 1.283–2.375) and anxiety/depression (OR = 1.380; 95% CI 1.013–1.879), which was in line with EQ-5D population health studies in both other countries and China [ 19 21 ] .Female patients with chronic hepatitis C tended to be fatigued and depressive [ 22 ], which might be the reason why they had worse HRQoL than males. What’s interesting we found was that patients from western China, who resided in less developed area of China, had significant higher EQ-VAS scores but more problems in self-care dimension, indicating that they considered themselves had relatively better health status, while their EQ-5D index didn’t show the same superiority.…”
Section: Discussionsupporting
confidence: 69%
“…Sociodemographic characteristics such as residence in the west of China, stable marital status, high family income have been found to be favorable to better quality of life for patients with HCV infection. Although the association between gender and HRQoL was not significant in our study, women still reported more problems in dimensions of pain/discomfort (OR = 1.746; 95% CI 1.283–2.375) and anxiety/depression (OR = 1.380; 95% CI 1.013–1.879), which was in line with EQ-5D population health studies in both other countries and China [ 19 21 ] .Female patients with chronic hepatitis C tended to be fatigued and depressive [ 22 ], which might be the reason why they had worse HRQoL than males. What’s interesting we found was that patients from western China, who resided in less developed area of China, had significant higher EQ-VAS scores but more problems in self-care dimension, indicating that they considered themselves had relatively better health status, while their EQ-5D index didn’t show the same superiority.…”
Section: Discussionsupporting
confidence: 69%
“…The impaired physical health of patients with HCV has been replicated using a wide variety of HRQOL and fatigue measures. Chronic fatigue syndrome (CFS) is unrelated to HCV infection and is generally severer than the fatigue experienced by HCV-infected patients (23). Fatigue in HCV is of central type and is associated with cognitive impairment and depression.…”
Section: Resultsmentioning
confidence: 99%
“…Yet several reasons support an investigation into fatigue symptoms in these individuals. First, the functional impairments associated with fatigue include considerable impairments and disability [13, 14] pointing to fatigue as an important target for treatment. Second, the cooccurrence of fatigue and psychiatric symptoms such as depression is linked to greater functional impairments than when it occurs alone [15, 16], suggesting that fatigue may aggravate current existing psychiatric conditions.…”
Section: Introductionmentioning
confidence: 99%